TEVHID-I TEDRISAT AND THE POLICY OF ISLAMIC TEACHER’S DEVELOPMENT IN TÜRKIYE (1924-1948) - Thoriquttyas, Titis (Journal of Religious Policy, 2024)
This study investigates the impact of the Tevhid-i Tedrisat Law on the development of religious education and teacher training in Türkiye, focusing on the law’s historical background, institutional restructuring, and influence on teacher development. Historically, Tevhid-i Tedrisat is a policy of "Educational Unification" in Türkiye that was inaugurated in 1924 to unite traditional Islamic education in madrasas and secular education in modern schools. This study addresses how Tevhid-i Tedrisat reshaped religious education, centralizing control under the Ministry of Education, and the resulting implications for religious education teachers’ roles and competencies. Utilizing historical institutionalism as a theoretical framework, this research adopts a qualitative approach, examining primary and secondary sources including government documents, academic literature, and archival records. The study reveals that Tevhid-i Tedrisat marked a paradigm shift, as religious education was secularized and integrated into a unified curriculum. Teacher training institutions, such as İlahiyat (Islamic Theology) faculties, were restructured to emphasize pedagogical skill and secular state values, yet gaps persisted in reaching rural areas and adapting to diverse student needs. The findings highlight the complexities of integrating religious education within a secular framework, where curriculum adjustments were influenced by cultural and political shifts. This transformation created both opportunities and limitations for teacher development, underscoring challenges in balancing secular pedagogy with cultural sensitivity. The study concludes that while Tevhid-i Tedrisat significantly shaped the foundation of Turkey’s educational system, ongoing teacher training reforms could benefit from localized adaptations, inclusive pedagogy, and historical awareness.